Clinical management of uterine cervical mullerian adenosarcoma: A clinicopathological study of six cases and review of the literature - Shinichi Togami; Toshihiko Kawamura; Mika Fukuda; Shintaro Yanazume; Masaki Kamio; Hiroaki Kobayashi (Elsevier, 2018)
Objective: To assess the clinicopathological characteristics and clinical management of patients diagnosed with mullerian adenosarcoma of the uterine cervix. Materials and methods: Records of six patients surgically treated for cervical mullerian adenosarcoma were reviewed. Results: The median age of the patients was 50 years (range, 17-74). Four patients presented with vaginal bleeding and two of them had watery discharge as the primary symptoms. Three nulliparous patients who hoped to preserve their uterus were included in this study and only one of the three patients received fertility-preservation surgery. Five patients underwent hysterectomy (simple in 3, modified radical in 2) with bilateral salpingo-oophorectomy or bilateral salpingectomy. One patient underwent conization of the cervix to preserve her fertility as there was no sarcomatous overgrowth, heterologous elements, or deep cervical stromal invasion. A recurrence of cervical mullerian adenosarcoma with sarcomatous overgrowth was observed in one patient who underwent simple hysterectomy. Conclusion: The presence of sarcomatous overgrowth and deep cervical stromal invasion are associated with poor prognosis. Along with adequate counseling, fertility-preservation surgery may be an acceptable option for exophytic cervical mullerian adenosarcoma in the cases that do not show sarcomatous overgrowth and deep cervical stromal invasion. Keywords: Clinicopathological characteristics, Fertility-preservation surgery, Mullerian adenosarcoma, Uterine cervix